The law of evidence in Nigeria - Aguda, T. Akinola (Ibadan : Spectrum, 1989)
The object of the book is to present in comprehensive manner ,the Nigerian law of evidence based mainly on the evidence Act cap 62 of the laws of the Federation of Nigeria and Lagos 1958
Includes index.
obn23/01/2019
Loans
Keywords: Evidence (Law)